2018
DOI: 10.1161/jaha.117.008032
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponins for the Diagnosis of Acute Myocardial Infarction in Chronic Kidney Disease

Abstract: Background Patients with chronic kidney disease ( CKD ) are at high risk of myocardial infarction. Cardiac troponins are the biomarkers of choice for the diagnosis of acute myocardial infarction ( AMI ) without ST ‐segment elevation ( NSTE ). In patients with CKD , troponin levels are often chronically elevated, which reduces their diagnostic utility when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 21 publications
0
70
0
Order By: Relevance
“…Diagnostic performance of dynamic change for highsensitivity cardiac troponin-T levels for the diagnosis of acute myocardial infarction. change in hs-cTnT increases the diagnostic accuracy for AMI in patients with CKD [29][30][31][32]. A study with 670 patients (undergoing regular hemodialysis presented with chest pain or dyspnea) proposed the optimal cutoff value of the relative changes in hs-cTnT after 3 h was 24% for the diagnosis of AMI [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic performance of dynamic change for highsensitivity cardiac troponin-T levels for the diagnosis of acute myocardial infarction. change in hs-cTnT increases the diagnostic accuracy for AMI in patients with CKD [29][30][31][32]. A study with 670 patients (undergoing regular hemodialysis presented with chest pain or dyspnea) proposed the optimal cutoff value of the relative changes in hs-cTnT after 3 h was 24% for the diagnosis of AMI [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study with 670 patients (undergoing regular hemodialysis presented with chest pain or dyspnea) proposed the optimal cutoff value of the relative changes in hs-cTnT after 3 h was 24% for the diagnosis of AMI [29]. Recently, a large prospective study showed that a relative change in hs-cTnT of 250% after 3 h could be used to rule in AMI, with a positive predictive value of 0.8 in patients with CKD who presented with chest pain [31]. Most studies enrolled patients with CKD or end-stage renal disease (ESRD) with typical chest pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…100 For example, a recent study in individuals with chronic kidney disease proposed algorithms where the relative change cut-off for hs-cTnI was 280% and for hs-cTnT was 250%, which are vastly different from the 20% cut-off defined by international recommendations. 101 Serial measurements of cTn over the long term may also be useful in providing prognostic information. 102 Measurable concentrations of cTn using hs-cTn assays in the general population have been associated with structural cardiac disease, cardiac failure, and an increased risk of both cardiovascular and all-cause mortality, even at concentrations well below the 99 th percentile value.…”
Section: Authormentioning
confidence: 99%
“…It is generally believed, therefore, that a diagnosis cannot rely only on a single increase of troponin (99th percentile)-dynamic observation would be more significant 15,16 . Continuous monitoring of hs-cTnT (during 3 to 6 h intervals) is helpful for distinguishing acute myocardial ischemia from noncardiac diseases 17 .…”
Section: Discussionmentioning
confidence: 99%